ln(2x^2 +9x-5) =1+ ln( x^2+2x-15)

Moving Ln to one side ln(2x^2 +9x-5) -  ln( x^2+2x-15) =1 Subtracting Ln is the same as dividing ln(((2x^2 +9x-5)/( x^2+2x-15)) ln((2x-1)/(x-3))=1 Taking e to both sides (2x-1)/(x-3)=e x=(1-3e)/(2-e)

Answered by Raj H. Maths tutor

7988 Views

See similar Maths GCSE tutors

Related Maths GCSE answers

All answers ▸

Solve the two simultaneous equations X2 +2Y2= 18 and X - Y = 3


Solve the following equation. (x)^2-8x+15=0


64^-1/3


solve this equation x^2 -2x=-1


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo

© MyTutorWeb Ltd 2013–2025

Terms & Conditions|Privacy Policy
Cookie Preferences